A Literature Review Determinat Factors of Quality of Life in Chronic Kidney Disease patients with Hemodialysis - Ni Wayan Sri Wahyuni; Ni Putu Kamaryati; Made Rismawan; Putu Inge Ruth Suantika (Babali Nursing Research)
Introduction: Patients with chronic renal failure who undergo hemodialysis have been found to have a decreased quality of life. A decrease in quality of life in patients with chronic renal failure who have to undergo hemodialysis is possible because they have not been able to accept the condition of the disease and the consequences they have to live with due to the disease. It is important for people with chronic renal failure to be able to maintain their quality of life so that they can still live well.Methods: The research design used in this study was a literature review. The literature review and evaluation protocol used the PRISMA checklist to determine the selection of studies that have been found and adjusted to the literature review. The literature review was conducted using five journal databases: ScienceDirect, Ebsco, PubMed, Neliti, and Google Scholar. The keywords in this literature review were matched with Medical Subject Heading (MeSH) consisting of “quality of life” AND “chronic renal failure disease” AND “determinants” AND “hemodialysis”. Several inclusion criteria were set to obtain eligible articles: published between 2015 and 2024, and written in English or Indonesian. A total of 16 eligible articles were finally included in the analysis. Results: From the literature review, it was found that some of the factors studied were demographic factors such as age, gender, education, hemodialysis duration, medication adherence, depression, complications, family support, income, nutritional status, hemoglobin levels, and comorbidities.Conclusion: From the results of the above study, several factors affect the quality of life of hemodialysis patients, namely the duration of hemodialysis, drug compliance, age, gender, education, occupation, gender, family support, nutritional status, depression, hemoglobin levels and comorbidities. For further research, it is hoped that it can conduct literature studies with other factors that have not been studied in this literature review so that later it can be known which factors are more influential and dominant in relation to the quality of life of patients with chronic kidney failure.